Enhanced noradrenergic activity in the amygdala contributes to hyperarousal in an animal model of PTSD. (August 2016) - Ronzoni, Giacomo; del Arco, Alberto; Mora, Francisco; Segovia, Gregorio
Highlights: IFS produces a long-term reduction of the response to a novel environment in rats. IFS increases evoked noradrenaline release in the amygdala. Amygdala propranolol injections normalize the behavior of IFS exposed rats. Abstract: Increased activity of the noradrenergic system in the amygdala has been suggested to contribute to the hyperarousal symptoms associated with post-traumatic stress disorder (PTSD). However, only two studies have examined the content of noradrenaline or its metabolites in the amygdala of rats previously exposed to traumatic stress showing inconsistent results. The aim of this study was to investigate the effects of an inescapable foot shock (IFS) procedure (1) on reactivity to novelty in an open-field (as an index of hyperarousal), and (2) on noradrenaline release in the amygdala during an acute stress. To test the role of noradrenaline in amygdala, we also investigated the effects of microinjections of propranolol, a β-adrenoreceptor antagonist, and clenbuterol, a β-adrenoreceptor agonist, into the amygdala of IFS and control animals. Finally, we evaluated the expression of mRNA levels of β-adrenoreceptors (β1 and β2) in the amygdala, the hippocampus and the prefrontal cortex. Male Wistar rats (3 months) were stereotaxically implanted with bilateral guide cannulae. After recovering from surgery, animals were exposed to IFS (10 shocks, 0.86 mA, and 6 s per shock) and seven days later either microdialysis or microinjections were performed in amygdala. Animals exposed to IFS showed a reduced locomotion compared to non-shocked animals during the first 5 min in the open-field. In the amygdala, IFS animals showed an enhanced increase of noradrenaline induced by stress compared to control animals. Bilateral microinjections of propranolol (0.5 μg) into the amygdala one hour before testing in the open-field normalized the decreased locomotion observed in IFS animals. On the other hand, bilateral microinjections of clenbuterol (30 ng) into the amygdala of control animals did not change the exploratory activity induced by novelty in the open field. IFS modified the mRNA expression of β1 and β2 adrenoreceptors in the prefrontal cortex and the hippocampus. These results suggest that an increased noradrenergic activity in the amygdala contributes to the expression of hyperarousal in an animal model of PTSD.